Detection of Selfish Nodes Through Reputation Model In Mobile Adhoc Network - MANET - et. al., Muruganantham Ponnusamy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The nodes are placed in open environment and moves randomly from one place to other are vulnerable to security threats in Mobile Adhoc Network (MANET). Therefore the node reputation and energy efficient model is applied in MANET that reduces the inconvenience created by selfish nodes and removes from the system during routing operation. The reputed and energy efficient nodes are identified from the network and the data transmission takes on reliable routes. However in this reputation scheme the malicious nodes are non co-operative with each other.-The reputed nodes are detected through the analysis of communication ratio between the nodes. The simulation result for the proposed model is discussed here and shows the efficiency achieved is better.